Komercjalizacja, prywatyzacja a podmioty administracji gospodarczej - Kocowski, Tadeusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Ownership changes in the economy and changes in organizational forms of public entities changed the legal forms of influence exerted on them by the authorities acting on behalf of the owner of the Treasury. Taking ownership functions by the authorities makes the antinomy which arises between the interests of the individual and society seem to fall. The administrative authority in exercising the function of corporate bodies should be guided by the public interest, but also its legitimate interest. In the case of privatization of public tasks, the interests of individual performers of these tasks should be consistent with the public interest.
Keywords: komercjalizacja; prywatyzacja; administracja gospodarcza